(3GdJSjjQ GdYedj hGdEJUGdGJ GdEOGQjI (B:s (3GdeaGgje hGdJWHjbGJ (B/s - (3fhQj, efjQs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2015)
(3JfGhd gPG GdcJGH eGgjI hCSGSjGJ GdJSjjQ GdYedj hCge JbfjGJg, HGdGVGaI Gdi eaghe GdEJUGdGJ GdEOGQjI HeG aj Pdc GdGLJeGYGJ hGdJhKjb hGdCQTaI hGdeQGSdGJ GdGOGQjI hJWHjbGJgG(B. s
Keywords: (3GdEJUGdGJ GdEOGQjI (B- (3GdLRGFQs; (3GdEOGQI GdYGeI (B- (3GdLRGFQs; (3GdeDSSGJ GdYGeI (B- (3EOGQI (B- (3GdLRGFQs